Level of Anxiety among Medical Students during COVID-19 Pandemic - Farah Rehman, Nayyara Tahir, Qurat Ul Ain, Hamid Mehmood, Tahir Mukhtar Sayed, Shamila Afshan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The general atmosphere of the medical college is frequently seen as being extremely stressful; as a result, medical students' academic results suffer, as well as their physical and psychological health. The purpose of this study was to evaluate medical students' levels of anxiety about their future careers. Objectives: To exploring the level of anxiety among medical students during COVID-19 Pandemic Methods: It was a descriptive quantitative cross-sectional research. After receiving verbal approval from each student at the Fatima Jinnah Medical University in Lahore, the participants enrolled. The data was gathered using a pre-designed questionnaire. A VAS score was employed to assess anxiety levels. SPSS 23 was used to analyze data. To get the desired findings, a statistical test like the chi-square test was used, with a p-value of 0.05 being considered statistically significant. Results: The results showed that the mean age student was 20.33± 1.49 years with range from 19-27 years of 165 female medical students were enrolled. Maximum strength of 3rd professional year as 70(42.42%), students were asked to respond to their own self-perceived level of anxiety by using VAS scale of 0 to 100 (mild, moderate and severe) and 84(50.91%) students’ shows severe level of anxiety. The factor contributing anxiety during COVID-19 explored and faced fear about future career 127(76.97%). Students observed that it took great effort to understand online lectures 108(65.45%) and faced the problem of recalling the memorized online 112(67.88%) as insignificant p-value. Conclusion: The COVID-19 epidemic did not seem to enhance the general degree of anxiety among medical students, but instead, they were more concerned about their studies, exams, and especially their future career. Keywords: Visual Analogue Scale, Exam Anxiety, Anxiety.